1980
DOI: 10.1007/bf02533888
|View full text |Cite
|
Sign up to set email alerts
|

A method for the quantitative estimation of cholesterol α‐oxide in eggs

Abstract: A method for the quantitation of cholesterol α‐oxide in egg and egg products is described. Total lipids extracted from dry egg samples were fractionated on a silicic acid column to concentrate cholesterol oxides which were then quantitatively determined by gas liquid chromatography (GLC). Those samples which showed cholesterol oxides by GLC were further analyzed by high pressure liquid chromatography (HPLC) for the ratio of cholesterol α‐oxide and cholesterol β‐oxide. Cholesterol α‐oxide content was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2
2

Year Published

1981
1981
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 9 publications
0
23
2
2
Order By: Relevance
“…Hot alkaline saponification to hydrolyze lipid matter (including sterol esters) is commonly employed to concentrate non-saponifiable sterols before analyses. This can cause certain oxidized sterols, notably isomeric epoxides and 7-ketone to decompose to various degrees (Chicoye et al, 1968b;Tsai et al, 1980;Smith, 1981), thereby generating the diene (cholesta-3,5-dien-7one) (Tsai and Hudson, 1984). The secondary oxidation product may have been erroneously identified in some instances as present in the original sample.…”
Section: Variation In Quantificationmentioning
confidence: 99%
“…Hot alkaline saponification to hydrolyze lipid matter (including sterol esters) is commonly employed to concentrate non-saponifiable sterols before analyses. This can cause certain oxidized sterols, notably isomeric epoxides and 7-ketone to decompose to various degrees (Chicoye et al, 1968b;Tsai et al, 1980;Smith, 1981), thereby generating the diene (cholesta-3,5-dien-7one) (Tsai and Hudson, 1984). The secondary oxidation product may have been erroneously identified in some instances as present in the original sample.…”
Section: Variation In Quantificationmentioning
confidence: 99%
“…Chicoye et al (1968) identified, but did not quantitate, five oxidation products in spray-dried egg yolk irradiated with both sunlight and fluorescent light. Tsai et al (1980) developed a method for quantitative estimation of cholesterol-5,6-epoxides (CEs) in eggs. Using this method, Tsai and Hudson (1985) quantitated CEs in commercially spraydried egg products.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue Lipid was determined by the method of Bligh and Dyer [11] with slight modification by Floch et.al [12]. Phospholipids [13], Cholesterol [14] and Triacylglycerol [15] were assayed by standard AOCS methods.…”
Section: Nutrient Analysismentioning
confidence: 99%